Ado-tratuzumab emtansine beyond breast cancer: therapeutic role of targeting other HER2-positive cancers - Zheng, Yang; Zou, Jiayu; Sun, Chen; Peng, Fu; Peng, Cheng (Frontiers in Molecular Biosciences, 2023)
Ado-trastuzumab emtansine (T-DM1) is a novel antibody-drug conjugate that was approved by the FDA in 2013 for advanced HER2-positive breast cancer treatment and had shown promising clinical benefits. However, HER2 overexpression and gene amplification have also been reported in other cancers like gastric cancer, non-small cell lung cancer (NSCLC), and colorectal cancer, etc. A large number of preclinical studies have also shown its significant anti-tumor effect on these HER2-positive tumors. With a deepening of research, a large number of clinical trials have been carried out. In this review, we briefly introduced the pharmacological effects of T-DM1 and reviewed its preclinical and clinical studies, especially in Other HER2+ Cancers, pointing out what has been encountered between its preclinical and clinical studies. In clinical, we found that T-DM1 does have a therapeutic value on a part of other cancers, but little effect was observed on gastric cancer and NSCLC, being inconsistent with the preclinical studies.